Queen's Park Hotel, Port of Spain, Trinidad - (:unkn) unknown (My University, 2010)
The Queen's Park Hotel, located in Port of Spain on the Southern side of the Queen's Park Savannah, was first opened in January 1895. This postcard, postmarked August 11th 1930, is addressed to Miss Francis Evans of North Carolina, United States of America.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; 1930; Historic hotels--Trinidad and Tobago; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Transportation--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)